Roger vivier - Mouzat, Virginie; Pringle, Colombe; Saillard, Olivier; Luna, Ian (New York : Rizzoli International Publications, 2013)
A gorgeous tribute to the legendary shoe and accessories designs of Roger Vivier. Master designer Roger Vivier elevated both the form and decoration of ladies' shoes during his sixty-year career. His innate Parisian style embodied a sense of perfection and craftsmanship, and his work was coveted by style icons from Elsa Schiaparelli to Jackie Onassis. Described by Yves St. Laurent as bringing to his work a "level of charm, delicacy, refinement and poetry unsurpassed," he created the first stiletto heel for a ready-to-wear shoe line with the house of Dior in 1955. His shoes are legendary, and the tradition of his innovative spirit continues with the revival of the house by current designer Bruno Frisoni, who has updated Vivier's concepts, bringing his own touch to signature shapes and embellishments (including the buckle pump made famous by Catherine Deneuve in Belle du Jour).
boek